Strangulation as an Acquired Brain Injury in Intimate–Partner Violence and Its Relationship to Cognitive and Psychological Functioning: A Preliminary Study. Issue 1 (January 2022) - Valera, Eve M.; Daugherty, Julia C.; Scott, Olivia C.; Berenbaum, Howard
Abstract : Objective: The aim of this work was to examine the relationship between strangulation-related alterations in consciousness (AIC) and cognitive and psychological outcomes in women who have experienced intimate partner violence (IPV). Setting: Participants were recruited from a variety of settings, including women's shelters and support programs. Participants: A total of 99 women were enrolled in the study. After applying exclusion criteria for factors that could mask or confound the effects of strangulation, 52 women remained for analyses. Design: Cross-sectional, retrospective. Main Measures: We used several cognitive measures to assess learning, long-term and working memory, visuomotor speed, cognitive flexibility, and nonverbal cognitive fluency as well as several psychological measures to assess posttraumatic stress symptomatology, general distress, worry, anhedonic depression, and anxious arousal. We also used the Brain Injury Severity Assessment interview to examine the association between strangulation-related AICs and these measures of cognitive and psychological functioning. Results: Women who had experienced strangulation-related AICs performed more poorly on a test of long-term memory ( P < .03) and had higher levels of depression ( P < .03) and posttraumatic stress symptomatology ( P < .02) than women who had not experienced strangulation-related AIC. When controlling for potential confounding variables, including number of IPV-related traumatic brain injuries, women who had experienced strangulation also performed more poorly on a measure of working memory. Conclusion: This is the first report to assess strangulation in this manner and demonstrate links to cognitive and psychological functioning. These preliminary data contribute to our knowledge of strangulation and its effects on women who have experienced IPV.